Daclatasvir and asunaprevir in hemodialysis patients with hepatitis C virus infection: a nationwide retrospective study in Japan - Suda, Goki; Furusyo, Norihiro; Toyoda, Hidenori; Kawakami, Yoshiiku; Ikeda, Hiroki; Suzuki, Michihiro; Arataki, Keiko; Mori, Nami; Tsuji, Keiji; Katamura, Yoshio; Takaguchi, Koichi; Ishikawa, Toru; et al. (Journal of gastroenterology, 2018)
Background Hepatitis C virus (HCV) infection is common in hemodialysis patients and worsens their prognosis, while antiviral therapy options are limited. Recently, clinical trial and real-world, small-scale studies have reported excellent responses to direct-acting antivirals in patients with advanced chronic kidney diseases. However, real-world, large-scale data were lacking. This large multicenter analysis included HCV-infected hemodialysis patients receiving combination therapy with a nonstructural protein 5A (NS5A) inhibitor, daclatasvir (DCV), and a protease inhibitor, asunaprevir (ASV). Methods Twenty-three centers in Japan participated in this study of 123 hemodialysis patients with genotype 1 HCV infection, who received DCV/ASV combination therapy between November 2014 and March 2016. We collected and analyzed data relating to treatment outcome, baseline clinical information, laboratory measurements (during and after the treatment), and adverse events. Results Thirty-nine patients (31.7%) had advanced liver fibrosis, 12 (9.8%) had histories of hepatocellular carcinoma (HCC), and 18 (14.6%) had baseline resistance-associated variants (RAVs) of NS5A. The overall sustained virological response (SVR)12 rate was 95.9% (118/123). Notably, all patients with HCC and 94.4% (17/18) of those with NS5A RAVs achieved SVR12. Significant factors associated with non-SVR were advanced fibrosis and the interleukin-28B non-TT genotype at rs8099917. Four patients (3.3%) discontinued therapy because of adverse events including elevated serum alanine transaminase levels ( n = 2), rash ( n = 1), and HCC ( n = 1); all of these achieved SVR12. Conclusions This real-world, nationwide study revealed that DCV/ASV combination therapy was safe and highly effective for hemodialysis patients with genotype 1 HCV infections. This study was registered at the UMIN Clinical Trials Registry (UMIN000024227).